OP272 Two-Year Within-Trial And Estimated Lifetime Cost Effectiveness Of The Weight Management Program In The Diabetes REmission Clinical Trial (DiRECT). (December 2020) - Xin, Yiqiao; Davies, Andrew; Briggs, Andrew; McCombie, Louise; Martina Messow, C.; Grieve, Eleanor; Leslie, Wilma S.; Taylor, Roy; Lean, Michael E. J.
Abstract : Introduction: Type 2 diabetes results mainly from weight gain in adult life and affects one in twelve people worldwide. In the Diabetes REmission Clinical Trial (DiRECT), the primary care-led Counterweight-Plus weight management program achieved remission of type 2 diabetes (for up to six years) for forty-six percent of patients after one year and thirty-six percent after two years. The objective of this study was to estimate the implementation costs of the program, as well as its two-year within-trial cost effectiveness and lifetime cost effectiveness. Methods: Within-trial cost effectiveness included the Counterweight-Plus costs (including training, practitioner appointments, and low-energy diet), medications, and all routine healthcare contacts, combined with achieved remission rates. Lifetime cost per quality-adjusted life-year (QALY) was estimated according to projected durations of remissions, assuming continued relapse rates as seen in year two of DiRECT and the consequent life expectancy, quality of life and healthcare costs. Results: The two-year intervention cost was EUR 1, 580 per participant, with over eighty percent of the costs incurred in year one. Compared with the control group, medication savings were EUR 259 (95% confidence interval [CI]: 166–352) for anti-diabetes drugs and EUR 29 (95% CI: 12–47) for anti-hypertensive medications. The intervention was modeled with a lifetime horizon to achieve a mean 0.06 (95% CI: 0.04–0.09) gain in QALYs for the DiRECT population and a mean total lifetime cost saving per participant of EUR 1, 497 (95% CI: 755–2, 331), with the intervention becoming cost-saving within six years. Conclusions: The intensive weight loss and maintenance program reduced the cost of anti-diabetes drugs through improved metabolic control, achieved diabetes remission in over one-third of participants, and reduced total healthcare contacts and costs over two years. A substantial lifetime healthcare cost saving is anticipated from periods of diabetes remission and delaying complications. Healthcare resources could be shifted cost effectively to establish diabetes remission services, using the existing DiRECT intervention, even if remissions are only maintained for limited durations. However, more research investment is needed to further improve weight-loss maintenance and extend remissions.